Cytoskeletal Dynamics in Epithelial-Mesenchymal Transition: Insights into Therapeutic Targets for Cancer Metastasis - Datta, Arpita (Cancers (Basel), 2021)
SIMPLE SUMMARY: The epithelial to mesenchymal transition (EMT) is a well-documented process in the study of cancer metastases. The cytoskeleton is an intricate network involved in various cellular activities and impacts cell shape, division, trafficking, and motility. However, several functions and activities of the cytoskeleton, which plays a pivotal role in EMT, are not fully understood. This review aims to provide significant insights into the cytoskeleton’s physiological functions and the crucial role in the EMT process. Our review focuses on the participation of actin filaments, intermediate filaments, and microtubules in promoting EMT and their influence on cancer metastasis. We have also highlighted potential therapeutic targets associated with EMT activation for clinical intervention. A better understanding of multi-drug resistance (MDR) mechanisms in cancer cells with the cytoskeleton could accelerate the discovery of new therapies for aggressive cancer. ABSTRACT: In cancer cells, a vital cellular process during metastasis is the transformation of epithelial cells towards motile mesenchymal cells called the epithelial to mesenchymal transition (EMT). The cytoskeleton is an active network of three intracellular filaments: actin cytoskeleton, microtubules, and intermediate filaments. These filaments play a central role in the structural design and cell behavior and are necessary for EMT. During EMT, epithelial cells undergo a cellular transformation as manifested by cell elongation, migration, and invasion, coordinated by actin cytoskeleton reorganization. The actin cytoskeleton is an extremely dynamic structure, controlled by a balance of assembly and disassembly of actin filaments. Actin-binding proteins regulate the process of actin polymerization and depolymerization. Microtubule reorganization also plays an important role in cell migration and polarization. Intermediate filaments are rearranged, switching to a vimentin-rich network, and this protein is used as a marker for a mesenchymal cell. Hence, targeting EMT by regulating the activities of their key components may be a potential solution to metastasis. This review summarizes the research done on the physiological functions of the cytoskeleton, its role in the EMT process, and its effect on multidrug-resistant (MDR) cancer cells—highlight some future perspectives in cancer therapy by targeting cytoskeleton.